The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jelechem.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Organic cyclisations of propargyl and allyl bromoesters in microemulsions catalysed by electrogenerated nickel(I) tetramethylcyclam

Abstract: While the reductive intramolecular cyclisation of propargyl and allyl bromoesters catalysed by [Ni(tmc)] + gives good yields of the desired products using N,N-dimethylformamide as the solvent, the use of this aprotic solvent presents practical, safety and environmental issues. This paper therefore reports the search for non-toxic alternatives, in particular the study of microemulsions prepared from water, hydrocarbons, surfactant and alcohol co-surfactant. It is shown that the [Ni(tmc)] 2+ /[Ni(tmc)] + couple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(59 reference statements)
2
6
0
Order By: Relevance
“…Rusling et al have reported free radical generation and coupling processes in bicontinuous microemulsion [17][18][19]. Similar electro generated free radical reactions have also been reported [20,21]. Electrochemical coupling of benzyl free radicals generated from benzyl bromide with active methylene compounds under galvanostatic experimental conditions in cationic microemulsions was reported from this laboratory [21].…”
Section: Introductionsupporting
confidence: 74%
“…Rusling et al have reported free radical generation and coupling processes in bicontinuous microemulsion [17][18][19]. Similar electro generated free radical reactions have also been reported [20,21]. Electrochemical coupling of benzyl free radicals generated from benzyl bromide with active methylene compounds under galvanostatic experimental conditions in cationic microemulsions was reported from this laboratory [21].…”
Section: Introductionsupporting
confidence: 74%
“…Electrogenerated nickel­(I) cyclam and nickel­(I) tetramethyl cyclam have been employed to carry out a variety of reductive cyclization reactions involving allyl 2-halophenyl ethers, propargyl and allyl bromoesters, and N -allyl-α-halo­amides …”
Section: Halogenated Environmental Pollutantsmentioning
confidence: 99%
“…bisphosphine, proceed via an inner-sphere pathway of metal-centered halogen atom abstraction. 32 Similarly, Ni(I) cyclam or tetramethylcyclam, a widely utilized redox mediator for RX reduction 30,[33][34][35][36] bearing no redox-active ligand, has been shown to catalyze the electroreduction of RX at potential values ~ 1 V more positive than the direct reduction of the substrate, rendering an OSET mechanism unlikely 37 . Yet, the nature of the oxidative addition adduct, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that RX oxidative addition processes at Ni­(I) complexes bearing a strongly sigma-donating and redox-inactive ligand, i.e., bisphosphine, proceed via an inner-sphere pathway of metal-centered halogen atom abstraction . Similarly, Ni­(I) cyclam or tetramethylcyclam, a widely utilized redox mediator for RX reduction , bearing no redox-active ligand, has been shown to catalyze the electroreduction of RX at potential values ∼1 V more positive than the direct reduction of the substrate, rendering an OSET mechanism unlikely . Yet, the nature of the oxidative addition adduct, i.e., halogen atom transfer vs two-electron oxidative insertion into the RX bond, , remains unresolved.…”
Section: Introductionmentioning
confidence: 99%